Learning together: Observation and other mechanisms which mediate shared practice contexts - Karlinsky, A. D.; Welsh, T.; Hodges, N. J. (Skill acquisition in sport: research, theory and practice, 2020)
Paired training seems to be at least as effective as individual training, while conferring some efficiency-related advantages. However, there are currently many unanswered questions with respect to when and why paired practice leads to motor learning benefits compared to individual practice. Part-task "interlocked" practice has been most robustly shown to support learning compared to individual practice, but such shared part-practice is not necessarily applicable for many sport skills. More relevant would be alternating or concurrent, whole-task forms of practice, where learners have the opportunity to observe a partner interspersed or simultaneous with their own physical practice of a complete skill. These types of practice scenarios have not proven to be so robust to paired practice benefits. Although there is some suggestive evidence that partners influence each other`s practice, and that there may be some beneficial interference conferred under some conditions (e.g., Karlinsky & Hodges, 2018a), there has not been strong evidence that for learning outcomes, paired practice is preferable to practice alone. Researchers and practitioners should consider how peers, especially those simply observing practice, could be more actively involved in the skill acquisition process (such as through peer-directed practice), not just to the potential benefit of the observer`s learning, but also as a means to provide informational (feedback) and/or motivational support to the physically active learner. There is much to be gained theoretically and practically by continued efforts to determine the factors that make paired (and team) learning a success and in future it will be important to complement behavioural measures with those probing psychological and neurophysiological processes, to provide a more thorough understanding of the mechanisms underpinning shared learning. Although we are hesitant to draw firm conclusions at this time about socialmotor learning conditions, we have provided a preliminary list of recommendations in a Table which could be used to guide practice and further empirical inquiry.